Antioxidants in Hops: Bioavailability, Health Effects and Perspectives for New Products - Corina-Aurelia Zugravu; Roxana-Elena Bohiltea; Teodor Salmen; Elena Pogurschi; Marina Ruxandra Otelea (MDPI AG, 2022)
Hop plant (Humulus lupulus L.) has been used by humans for ages, presumably first as a herbal remedy, then in the manufacturing of different products, from which beer is the most largely consumed. Female hops cones have different useful chemical compounds, an important class being antioxidants, mainly polyphenols. This narrative review describes the main antioxidants in hops, their bioavailability and biological effects, and the results obtained by now in the primary and secondary prevention of several non-communicable diseases, such as the metabolic syndrome related diseases and oncology. This article presents in vitro and in vivo data in order to better understand what was accomplished in terms of knowledge and practice, and what needs to be clarified by additional studies, mainly regarding xantohumol and its derivates, as well as regarding the bitter acids of hops. The multiple protective effects found by different studies are hindered up to now by the low bioavailability of some of the main antioxidants in hops. However, there are new promising products with important health effects and perspectives of use as food supplements, in a market where consumers increasingly search for products originating directly from plants.